CELL CULTURES PURITY CONTROL BY METHODS OF CLINICAL DIAGNOSTICS - Morozova, A V; Borchsenius, S N; Vishnyakov, I E; Malinin, A Yu (T͡S︡itologii͡a, 2017)
Cell cultures of higher organisms, especially cultures of human cells, are increasingly used in medical, pharmaceutical and scientific research. The main problem of cell cultures — non-lethal hidden contamination by mycoplasmas, viruses and outsider cell lines. As an available and reliable method for monitoring the purity of the cell cultures, we offer to use PCR kits designed and officially used in clinical diagnostics. We have tested 50 human cell lines using commercial diagnostic systems for detection of papilloma viruses, herpes viruses, adenoviruses, Mycoplasma hominis and total bacterial mass. Contamination in tested cell lines was not found. In the case of cell lines that contain integrated parts of viral genomes, the presence of the respective DNA sequences was confirmed. The proposed diagnostic systems can be effectively used to control the purity of cell lines, for qualitative detection of possible contamination, as well as for quantitative evaluations with calculation of viral load like it is practiced in clinical diagnostics.